2008
DOI: 10.4314/tjpr.v7i4.14700
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-vitro</i> Antimicrobial and Antitumor Activities of <i>Stevia Rebaudiana</i> (Asteraceae) Leaf Extracts

Abstract: Purpose:The purpose of the study is to evaluate the antimicrobial and antitumor activities of Stevia rebaudiana (Asteraceae) leaf extracts. Methods: Four solvent extracts (ethyl acetate, acetone, chloroform and water) of Stevia rebaudiana leaves were investigated against Staphylococcus aureus, Salmonella typhi, Escherichia coli, Bacillus subtilis, Aeromonas hydrophila and Vibrio cholerae by using agar well diffusion method. Candida albicans, Cryptococcus neoformans, Trichophyton mentagrophytes and Epidermophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 21 publications
3
64
2
9
Order By: Relevance
“…1-D). These results were also observed by Ghosh et al and Jayaraman et al who found that various solvent extracts of Stevia rebaudiana leaves could inhibit some bacteria and fungal, but no explanation was provided (Ghosh et al, 2008;Jayaraman et al, 2008). In addition, some researchers mentioned that the secondary metabolite "Stevioside" of RA may be responsible for the antimicrobial activity (Debnath, 2008).…”
Section: Sequencing Of Dgge Bandssupporting
confidence: 71%
“…1-D). These results were also observed by Ghosh et al and Jayaraman et al who found that various solvent extracts of Stevia rebaudiana leaves could inhibit some bacteria and fungal, but no explanation was provided (Ghosh et al, 2008;Jayaraman et al, 2008). In addition, some researchers mentioned that the secondary metabolite "Stevioside" of RA may be responsible for the antimicrobial activity (Debnath, 2008).…”
Section: Sequencing Of Dgge Bandssupporting
confidence: 71%
“…The leaves of this plant has a pleasantly sweet and refreshing taste which is educe by diterpene glycosides (stevioside and rebaudiosides), a high-potency sweeteners and substitute to sugar, being 300 times sweeter than sucrose (Madan et al, 2010;Megeji et al, 2005;Singh and Rao, 2005;Soejarto et al, 1983;Soejarto DD, Kinghorn AD, 1982;Yadav et al, 2011). Stevia is a well-known therapeutic agent serve as an efficient medication for diabetes, hypertension, myocardial and antimicrobial infections, dental troubles, and tumors (Chan et al, 1998;Gregersen et al, 2004;Jayaraman et al, 2008;Jeppesen et al, 2003Jeppesen et al, , 2002Kujur et al, 2010;Marcinek and Krejpcio, 2016;Muanda et al, 2011;Philippe et al, 2014;Planas and Kucacute, 1968;Shivanna et al, 2013;Šic Žlabur et al, 2013;Singh et al, 2015). In present time people are very calorie conscious which increases use of stevia in preparation of non-calorie food stuffs and become a major sweetening agent in food products in South-east Asia (Ashwell,billion US dollar.…”
Section: Introductionmentioning
confidence: 99%
“…Jayaraman i wsp. [16] analizowali właściwości czterech ekstraktów liści stewii. Najbardziej efektywny w przypadku bakterii był ekstrakt acetonowy (zwłaszcza w odniesieniu do bakterii G+), następnie ekstrakt na bazie octanu etylu.…”
Section: Działanie Na Drobnoustrojeunclassified